Midazolam as an antiemetic in patients receiving epidural morphine for postoperative pain relief - Elhakim, MD, Mokhtar; Elfattah, MD, Hany Abd; El-Din, MD, Dalia Nasr; El-Kabarity, MD, Reem; Atef, MD, Azia; El-Fakey, MD, Atef (Journal of Opioid Management, 2018)
Purpose: Epidural morphine has been associated with a significant incidence of postoperative nausea and vomiting (PONV). The authors have evaluated the prophylactic effects of midazolam in preventing nausea and vomiting following epidural morphine for postoperative pain control. Methods: The authors studied 80 women (n = 40 in each group) undergoing total abdominal hysterectomy under epidural anesthesia, in a randomized, double-blind, placebo-controlled study. At the end of the surgery, all patients received epidural morphine 3 mg for postoperative pain. Before morphine injection, the midazolam group received lowdose midazolam infusion (1 mg bolus followed by 1 mg h-1), while the placebo group received IV saline. Results: Patients in the midazolam group reported a lower incidence of total PONV, and a lower frequency of rescue antiemetic request than those in the placebo group (p < 0.05). In addition, midazolam was associated with a reduced incidence of pruritus following epidural morphine (p < 0.05). Conclusion: The authors conclude that low-dose midazolam infusion is effective in the prevention of nausea, vomiting, and pruritus following epidural morphine for postoperative pain control.